IDEOLOGICAL STRUGGLE ON USE OF CONSTRUCTION MATERIALS BALINESE TRADITIONAL BUILDING IN ERA DISRUPTED - Suyoga, I Putu Gede; Juliasih, Ni Ketut Ayu (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Ecological ideology seems to be a unity in the design of traditional Balinese architecture whose main construction is made of wood. The provisions of wood which may or may not or are good and which are prohibited to be used as building materials have been regulated in Balinese traditional architecture. This article is a qualitative research with an interpretive descriptive approach. Literature study was carried out on the translation of the contents of Asta Kosala Kosali, Janantaka and Taru Pramana manuscript especially about wood as building material. Interviews from informants were chosen purposively. This study finally revealed the ecological ideology underlying the construction of traditional Balinese buildings, under pressure from market ideology in the current era. The market ideology as emic has suppressed ecological ideology as an element of ethics, so the scarcity of availability of several types of local wood in building materials is inevitable